Penggunaan Technical Analysis dalam Memprediksi Pergerakan Harga Saham untuk Pengambilan Keputusan Investasi Saham - Prasetyo, Aries Heru (Jurnal Widya Manajemen & Akuntansi, 2003)
This research analyzes the use of technical analysis in predicting stock's price in order to set the best instrument decisions. The objects used in this analysis was PT. Telekomunikasi Indonesia Tbk and PT. Semen Gresik Tbk. The analysis is based on both quantitative and qualitative method. The clossing price for each stock was analyzed with : moving average methods, relative Strength Index and graphical methods. Consequently, the result of this research indicate that there was several weaknesses in the application of each methods. Two of the important factors which have to be considered in investment decisions are insting and experience over the past trading periods.